Interactive effect of temperature, acidification and ammonium enrichment on the seagrass Cymodocea nodosa. (September 2018) - Egea, L.G.; Jiménez-Ramos, R.; Vergara, J.J.; Hernández, I.; Brun, F.G.
Abstract: Global (e.g. climate change) and local factors (e.g. nutrient enrichment) act together in nature strongly hammering coastal ecosystems, where seagrasses play a critical ecological role. This experiment explores the combined effects of warming, acidification and ammonium enrichment on the seagrass Cymodocea nodosa under a full factorial mesocosm design. Warming increased plant production but at the expense of reducing carbon reserves. Meanwhile, acidification had not effects on plant production but increased slightly carbon reserves, while a slight stimulation of net production and a slight decrease on carbon reserves under ammonium supply were recorded. When all the factors were combined together improved the production and carbon reserves of Cymodocea nodosa, indicating that acidification improved ammonium assimilation and buffered the enhanced respiration promoted by temperature. Therefore, it could indicate that this temperate species may benefit under the simulated future scenarios, but indirect effects (e.g. herbivory, mechanical stress, etc.) may counteract this balance. Highlights: A significant synergy can occur when several environmental factors interact. Warming positively affect plant production but at expense of reducing carbon reserves. Loss leaf rates increased with ammonium supply CO2 increase did not produce significant effects. Future scenarios may benefit to C. nodosa improving their growth and carbon reserves.